Flora palinológica de la cuenca media del río San Eugenio, Risaralda (Cordillera Central), Colombia (2015)
ABSTRACT: A palynological atlas of the middle San Eugenio river drainage (Risaralda), Colombia is presented in order to established points of reference for future palynological studies of the Colombian Andes during the quaternary period. The study species were selected from two forest patches used RAP methods, one a forest fragment and the other section of riparian forest. In addition, we completed the list by including information contained in floristics surveys that were conducted near this study area. The pollen samples were processed and described using conventional methods of acetolysis and light microscopy. In total, 31 plant species distributed in 16 families that are characteristic of sub-Andean forests were described. The sites studied were characterized as disturbed forest fragments with successional vegetative elements. In addition, polen grains from domesticated species such as Manihot esculenta, Phaseolus sp., and Zea mays were included.